Optimalisasi Keterampilan Mengajar Guru PAI Berbasis Kompetensi Profesional dan Pedagogik - Hasan, Salim; Bazith, Akhmad; Wakka, Ahmad; Assegaf, Abd. Rauf (Journal of Gurutta Education, 2024)
This study aims to analyze teacher professionalism and professionality as professional educators. The problem examined is the competencies that professional teachers must possess according to the mandate of the law. The method used is a literature study by examining various sources related to teacher professionalism. The results show that professional teachers must master four main competencies, namely pedagogical, professional, social, and personality competencies. Teacher professionalism is determined by the quality of attitudes towards the profession and the level of knowledge and expertise possessed. Teacher competence is a combination of knowledge, skills, values, and attitudes reflected in habits of thinking and acting. It can be concluded that increasing teacher professionalism requires comprehensive mastery of competencies and development of positive attitudes towards the teaching profession. Efforts to improve teacher competence and qualifications need to be carried out continuously to realize quality education.